Exercise-mediated wall shear stress increases mitochondrial biogenesis in vascular endothelium. - Boa Kim; Hojun Lee; Keisuke Kawata; Joon-Young Park (PLoS ONE, 2014)
Enhancing structural and functional integrity of mitochondria is an emerging therapeutic option against endothelial dysfunction. In this study, we sought to investigate the effect of fluid shear stress on mitochondrial biogenesis and mitochondrial respiratory function in endothelial cells (ECs) using in vitro and in vivo complementary studies.Human aortic- or umbilical vein-derived ECs were exposed to laminar shear stress (20 dyne/cm2) for various durations using a cone-and-plate shear apparatus. We observed significant increases in the expression of key genes related to mitochondrial biogenesis and mitochondrial quality control as well as mtDNA content and mitochondrial mass under the shear stress conditions. Mitochondrial respiratory function was enhanced when cells were intermittently exposed to laminar shear stress for 72 hrs. Also, shear-exposed cells showed diminished glycolysis and decreased mitochondrial membrane potential (ΔΨm). Likewise, in in vivo experiments, mice that were subjected to a voluntary wheel running exercise for 5 weeks showed significantly higher mitochondrial content determined by en face staining in the conduit (greater and lesser curvature of the aortic arch and thoracic aorta) and muscle feed (femoral artery) arteries compared to the sedentary control mice. Interestingly, however, the mitochondrial biogenesis was not observed in the mesenteric artery. This region-specific adaptation is likely due to the differential blood flow redistribution during exercise in the different vessel beds.Taken together, our findings suggest that exercise enhances mitochondrial biogenesis in vascular endothelium through a shear stress-dependent mechanism. Our findings may suggest a novel mitochondrial pathway by which a chronic exercise may be beneficial for vascular function.